Evidence on the Use of Mouthwash for the Control of Supragingival Biofilm and Its Potential Adverse Effects - Shoji Takenaka; Maki Sotozono; Naoto Ohkura; Yuichiro Noiri (MDPI AG, 2022)
Antimicrobial mouthwash improves supragingival biofilm control when used in conjunction with mechanical removal as part of an oral hygiene routine. Mouthwash is intended to suppress bacterial adhesion during biofilm formation processes and is not aimed at mature biofilms. The most common evidence-based effects of mouthwash on the subgingival biofilm include the inhibition of biofilm accumulation and its anti-gingivitis property, followed by its cariostatic activities. There has been no significant change in the strength of the evidence over the last decade. A strategy for biofilm control that relies on the elimination of bacteria may cause a variety of side effects. The exposure of mature oral biofilms to mouthwash is associated with several possible adverse reactions, such as the emergence of resistant strains, the effects of the residual structure, enhanced pathogenicity following retarded penetration, and ecological changes to the microbiota. These concerns require further elucidation. This review aims to reconfirm the intended effects of mouthwash on oral biofilm control by summarizing systematic reviews from the last decade and to discuss the limitations of mouthwash and potential adverse reactions to its use. In the future, the strategy for oral biofilm control may shift to reducing the biofilm by detaching it or modulating its quality, rather than eliminating it, to preserve the benefits of the normal resident oral microflora.